Solitary bee larvae modify bacterial diversity of pollen provisions in the stem-nesting bee, Osmia cornifrons (Megachilidae) - Kueneman, Jordan G.; Gillung, Jessica; Van Dyke, Maria T.; Fordyce, Rachel F.; Danforth, Bryan N. (Frontiers in Microbiology, 2023)
Microbes, including diverse bacteria and fungi, play an important role in the health of both solitary and social bees. Among solitary bee species, in which larvae remain in a closed brood cell throughout development, experiments that modified or eliminated the brood cell microbiome through sterilization indicated that microbes contribute substantially to larval nutrition and are in some cases essential for larval development. To better understand how feeding larvae impact the microbial community of their pollen/nectar provisions, we examine the temporal shift in the bacterial community in the presence and absence of actively feeding larvae of the solitary, stem-nesting bee, Osmia cornifrons (Megachilidae). Our results indicate that the O. cornifrons brood cell bacterial community is initially diverse. However, larval solitary bees modify the microbial community of their pollen/nectar provisions over time by suppressing or eliminating rare taxa while favoring bacterial endosymbionts of insects and diverse plant pathogens, perhaps through improved conditions or competitive release. We suspect that the proliferation of opportunistic plant pathogens may improve nutrient availability of developing larvae through degradation of pollen. Thus, the health and development of solitary bees may be interconnected with pollen microbial diversity and perhaps with the propagation of plant pathogens.